Armored eaudiobook - Greaney, Mark (Armored, 2022)
A novel inspired by #1 New York Times best-selling author Mark Greaney’s Audible Original drama, Armored . Joshua Duffy is a Close Protection Agent—a professional bodyguard—and he's one of the world's elite operatives. That is, he was until his last mission in Lebanon. Against all odds, Josh got his primary out alive, but the cost was high. Josh lost his lower left leg.    There's not much call for an elite bodyguard with such an injury. So, Josh has to support his family working as a mall cop in New Jersey. For a man like Josh, this is purgatory on earth, but miracles can occur even in Paramus.    A lucky run-in with an old comrade promises to get Josh back in the field for one last job. The UN is sending a peace mission into the Sierra Madre mountains in Mexico, an area so dangerous it's known as Espinazo del Diablo— the Devil's Spine. Only a fool would think they could broker peace between the homicidal drug cartels in the region, and only a madman would sign on to keep those fools alive.